2019
DOI: 10.3174/ajnr.a6002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unruptured Distal Anterior Circulation Aneurysms with Flow-Diverter Stents: A Meta-Analysis

Abstract: BACKGROUND: The safety and efficacy of flow diversion among distal anterior circulation aneurysms must be proved. PURPOSE: Our aim was to analyze the outcomes after flow diversion among MCA, anterior communicating artery, and distal anterior cerebral artery aneurysms. DATA SOURCES: A systematic search of 3 databases was performed for studies published from 2005 to 2018. STUDY SELECTION: According to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we included studies reporting flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
8
42
1
Order By: Relevance
“…56 Previous authors have recommended to slightly oversize FD selection for highly tortuous vessels to account for device foreshortening 44 ; however, this can lead to lengthening of the FD, decreasing its metal coverage and increasing porosity, thus decreasing its effectiveness. This was observed in a meta-analysis by Cagnazzo et al for distal aneurysms using previous generations of FDs, in which a higher occlusion trend was observed with the use of multiple FD than single FD in 484 treated aneurysms (OR 2.3, 95% CI 0.8 to 7.2; p=0.08), 55 likely associated with device oversizing.…”
Section: Flow Diverters At and Beyond To The Circle Of Willismentioning
confidence: 65%
See 1 more Smart Citation
“…56 Previous authors have recommended to slightly oversize FD selection for highly tortuous vessels to account for device foreshortening 44 ; however, this can lead to lengthening of the FD, decreasing its metal coverage and increasing porosity, thus decreasing its effectiveness. This was observed in a meta-analysis by Cagnazzo et al for distal aneurysms using previous generations of FDs, in which a higher occlusion trend was observed with the use of multiple FD than single FD in 484 treated aneurysms (OR 2.3, 95% CI 0.8 to 7.2; p=0.08), 55 likely associated with device oversizing.…”
Section: Flow Diverters At and Beyond To The Circle Of Willismentioning
confidence: 65%
“…The small size of parent vessels (diameter ≤3 mm) and the presence of important divisions and branches represent a risk for ischemic complications when using FD. 38 53 54 Although promising results have been observed with the use of FD in distal aneurysms with occlusion rates up to 82%, 55 clinical and technical complications still exist. In a single center experience, 8.3% of patients developed postoperative ischemic stroke following PED placement in the A1 segment.…”
Section: Flow Diverters At and Beyond To The Circle Of Willismentioning
confidence: 99%
“…In our case, endovascular stent-assisted coiling allowed safe exclusion of pericallosal dissecting aneurysm from circulation, and the implanted stent enabled reconstruction of the parent artery, restoring the normal lumen diameter. The second considered endovascular treatment option was implantation of a flow-diverted stent into the pericallosal artery [ 8 , 9 ]. However, we found this method to be riskier, causing more potential complications due to the need to use greater force to deliver a larger microcatheter and flow diverter stent into the pericallosal artery with coexisting artery stenosis and not completely cured ACoA aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a procedural complication rate of 7.7% and 95% rate of good clinical outcome among 60 patients with available clinical follow-ups. Two systematic reviews and meta-analyses reported the feasibility and high efficacy of FDS for the treatment of aneurysms on small or distal vessels but with non-negligible complication rate (Cagnazzo et al, 2019 ; Yan et al, 2018 ). The results of these systematic reviews are, however, limited by the selection and publication bias of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Flow diverter stents (FDS) are now important tools in the neurointerventional armamentarium expanding the spectrum of treatable aneurysms by endovascular means. Although initially developed for the treatment of side-wall aneurysms of the internal carotid artery (ICA), their use has been increasingly expanding to include lesions involving smaller and more distal vessels, bifurcation aneurysms and also for treatment of challenging pathologies such as dissecting, fusiform, and blood-blister aneurysms (Puri et al, 2016 ; Cagnazzo et al, 2019 ; Bhogal et al, 2018 ; Saleme et al, 2014 ; Gawlitza et al, 2016 ; Rouchaud et al, 2015 ; Bhogal et al, 2017 ; Limbucci et al, 2020 ). This expansion of the spectrum of treatable lesions was invariably associated with the need for technical improvement of FDS such as better navigability, lower profile and the compatibility with small microcatheters to enable better and safer distal navigation.…”
Section: Introductionmentioning
confidence: 99%